A liberdade de expressão e os discursos de ódio em Ronald Dworkin: os espinhos ocultos do ouriço - Matheus Henrique Evangelista Felicio (2022)
This dissertation develops around the tension between freedom of expression and hate speech. An American matrix asserts that even in discriminatory manifestations speech must be ensured. Ronald Dworkin, a well-known philosopher of law, is the fruit of this conception. Despite supporting an egalitarian liberalism, that is, that the State must treat everyone with equal consideration and respect, it admits that freedom of expression must be ensured even in controversial cases that express hatred, discrimination and prejudice. Its foundations, in close synthesis, demonstrate how illegitimate it is for the State to deprive the citizen of expressing what he desires. Dworkin relies on understanding rights in a strong sense, ethical independence and special rights to justify this position of honor of freedom of expression. On the other hand, R. Dworkin has other elements and conceptions throughout his academic trajectory that apparently act differently from the acceptance of hate speech in the public sphere. These are the specific conceptions developed about: morals, responsibility, ethical independence and associative obligations. This dissertation, therefore, evaluates how much freedom of expression that admits hate speech fits these conceptions. In conclusion, freedom of expression cannot be sustained in conjunction with these elements, as they act under the moral imperative of "objective respect for the other", contrary to what hate speech advocates. Therefore, Dworkin must give up the right to freedom of expression that includes hate speech to align with the unifying project exposed in Justice for Hedgehogs. The perspective of analysis of this dissertation is internal to Dworkin's thought, that is, it dialogues with dworkinian concepts themselves. In order to dialogue between national peers, in addition to this discussion, this dissertation proposes to present alternatives to alexyana weighting in dealing with the tension between freedom of expression and hate speech, which is predominant in the Brazilian judiciary in the resolution of conflicts. I proposed that Dworkinian theory, when viewed in a better light, can lead us to deny hate speech, different from what Dworkin himself proposes. Thus, I consider that Dworkin's theory has elements philosophically sophisticated enough to deny the right to express hatred and, thus, justify Brazilian judicial decisions on the subject that has been receiving criticism from broad social sectors.